IbM Kelompok Petani Tebu Rakyat di Kecamatan Semboro, Kabupaten Jember - Ummi Sholikhah; Imam Sholahuddin (UII, 2015)
Sub-district Semboro is a strategic region for the development of sugarcane Agricultural commodities. According to the Central Bureau of Statistics Jember in 2008, the area under sugarcane cultivation in the district Semboro in 2008 approximately 491 acres, in the District Semboro also contained relatively large sugar mills and has the ability milling capacity of 70 thousand quintals or 7000 TCD ( Tones Cine Day ) with the extensive area of sugarcane commodities land, the availability of seed cane is also needed single bud planting method that is one of the breakthrough to overcome the problems in the nursery. In principle, a single bud planting method is to use a chip nursery development / potray with the buds. This can save planting materials, land and time in the nursery and produce quality seeds.In the early stages of implementation IbM activities that began in April 2014 until now is still running smoothly without significant obstacles, so that every transfer of science and technology that is given to the partners can be accepted and implemented, plan future activities are the stages of the transfer of seed cane single bud results in PII in moving to production fields, and will be doing the evaluation of any activity undertaken. Keywords: IbM, Semboro , Single Bud Planting